0 votes
23 views
in Polynomials by (45.2k points)
closed by

If a + b + c = 0, then prove that a3 + b3 + c3 = 3abc.

1 Answer

+1 vote
by (44.6k points)
selected by
 
Best answer

Given a + b + c = 0 

⇒ a + b = -c ……………..(1)

Cubing on both sides 

(a + b)3 = (-c)3 

a3 + b3 + 3ab (a + b) = -c3

a3 + b3 + 3ab (-c) =-c3 From(l) 

a3 + b3 – 3abc = -c3 

a3 + b3 + c3 – 3abc

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

...